The Strength of OVO Digital Wallet on Effect of Online Sales toward Purchasing Decisions - Alief Yudha Kurniawan; Pudjo Sugito; Christina Sri Ratnaningsih (University of Merdeka Malang, 2022)
This study aims to analyze the strength of effect online sales on purchasing decisions, analyze the effect of online sales on the OVO digital wallet, analyze the effect of the OVO digital wallet on purchasing decisions, analyze the mediating function of the OVO digital wallet on the effect of online sales on purchasing decisions. The sampling technique used accidental sampling technique with e-questionare as the main data collection tool. Based on the primary data from 60 respondents who were collected and analyzed using Smart Partial Least Square (PLS) data processing program, it was revealed that online sales significantly effect the purchasing decision, and it was also revealed that ovo digital wallet significantly mediates the interrelationship. Therefore, the results of this study provide important information for business entities as well as for other researchers who will conduct further research related to purchasing decisions. Also, the results of this research can certainly be generalized, whenever, of course, other research is needed with different objects and populations.